2017
DOI: 10.1140/epjc/s10052-017-5265-z
|View full text |Cite
|
Sign up to set email alerts
|

Particle states of lattice QCD

Abstract: We determine the degeneracy factor and the average particle mass of particles that produce the lattice QCD pressure and specific entropy at zero baryon chemical potential. The number of states of the gluons and the quarks are found to converge above T = 230 MeV to almost constant values, close to the number of states of an ideal quark-gluon phase, while their assigned masses retain high values. The number of states and the average mass of a system containing quarks in interaction with gluons are found to decre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…This suggests that chiral restoration is completed well before quarks are "dissolved" to independent entities. (b) In [5] an equivalent description of the Lattice results at vanishing baryonic density has been carried out, using one particle state with mass and degeneracy factor calculated from the fit to these results. It was found that the quark-gluon interacting system, when crossing the critical temperature T c , exhibits an abrupt decrease in the degeneracy factor and, also, in the respective mass.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that chiral restoration is completed well before quarks are "dissolved" to independent entities. (b) In [5] an equivalent description of the Lattice results at vanishing baryonic density has been carried out, using one particle state with mass and degeneracy factor calculated from the fit to these results. It was found that the quark-gluon interacting system, when crossing the critical temperature T c , exhibits an abrupt decrease in the degeneracy factor and, also, in the respective mass.…”
Section: Introductionmentioning
confidence: 99%